2012
DOI: 10.1124/jpet.112.201798
|View full text |Cite
|
Sign up to set email alerts
|

High-Throughput Identification and Characterization of Novel, Species-selective GPR35 Agonists

Abstract: Drugs targeting the orphan receptor GPR35 have potential therapeutic application in a number of disease areas, including inflammation, metabolic disorders, nociception, and cardiovascular disease. Currently available surrogate GPR35 agonists identified from pharmacologically relevant compound libraries have limited utility due to the likelihood of off-target effects in vitro and in vivo and the variable potency that such ligands exhibit across species. We sought to identify and characterize novel GPR35 agonist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 37 publications
1
34
0
Order By: Relevance
“…; Neetoo‐Isseljee et al. ) as well as for allosteric modulators of the mGluR1 receptor, another family C GPCR (Knoflach et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…; Neetoo‐Isseljee et al. ) as well as for allosteric modulators of the mGluR1 receptor, another family C GPCR (Knoflach et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…Compound 1 {4‐[(Z)‐[(2Z)‐2‐(2‐fluorobenzylidene)‐4‐oxo‐1,3‐thiazolidin‐5‐ylidene]methyl] benzoic acid} is described in Neetoo‐Isseljee et al . (25). Bufrolin [5,6‐dimethyl‐2‐nitro‐1H‐indene‐1,3(2H)‐dione] is described in Mackenzie et al .…”
Section: Methodsmentioning
confidence: 99%
“…4B). We and others have reported that many compounds first identified as ligands at human GPR35, including zaprinast, display markedly different potency and/or activity at rodent orthologs (Taniguchi et al, 2006;Jenkins et al, 2010Jenkins et al, , 2012Funke et al, 2013;Neetoo-Isseljee et al, 2013). We next examined the activity of a variety of mast cell stabilizers at the rat ortholog of GPR35 in the BRET-based b-arrestin-2 interaction assay.…”
Section: Compoundmentioning
confidence: 99%
“…Although GPR35 is indicated to be a receptor responsive to the endogenously produced tryptophan metabolite kynurenic acid (Wang et al, 2006), lack of convergence on this issue has resulted in a number of efforts to identify surrogate agonist ligands that might be used to help further define the roles of this receptor. Although a number of such ligands have been identified (Taniguchi et al, 2006;Jenkins et al, 2010;Zhao et al, 2010;Deng et al, 2012;Funke et al, 2013;Neetoo-Isseljee et al, 2013), many of these are either of modest potency and/or display markedly different potency at human and rodent orthologs of GPR35 (Jenkins et al, 2010;Funke et al, 2013;Neetoo-Isseljee et al, 2013). This has posed challenges both in efforts to define the orthosteric binding pocket of the receptor and to use rodents and cell lines derived from such animals to further explore the function of GPR35.…”
Section: Introductionmentioning
confidence: 99%